2022
DOI: 10.1177/07419325221125890
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Characteristics of Students With Emotional Disturbance in Special Education Research

Abstract: We conducted a systematic literature review examining the participant characteristics of studies of students with emotional disturbance (ED) with the purpose of better understanding potential similarities and differences between students with ED in research and the population of students with ED. Results indicate (a) participants with reported demographics were predominantly White or Black/African American and male; (b) participants in research samples were significantly different from the national population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The reasons for this are beyond the scope of this review but could be explained by any number of factors, including a difference in history of supports between groups and the type and intensity of interventions used for children with and without disabilities. Though tangential to the primary purpose of this review, our findings align with other reviews that document lack of reporting of race (60% not reported) and ethnicity (over 80% not reported) in special education research (Chow et al, 2022;Robertson et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…The reasons for this are beyond the scope of this review but could be explained by any number of factors, including a difference in history of supports between groups and the type and intensity of interventions used for children with and without disabilities. Though tangential to the primary purpose of this review, our findings align with other reviews that document lack of reporting of race (60% not reported) and ethnicity (over 80% not reported) in special education research (Chow et al, 2022;Robertson et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…However, the incongruence of interventions with Black populations has not been adequately addressed (Graves et al, 2021). Specifically, we need to consider whether an intervention has been designed, tested, and developed with the population the intervention will be used for (Chow et al, 2022; Steinbrenner et al, 2022). The generalization of an intervention can be limited if we do not examine whether an intervention is differentially effective.…”
Section: Shifting Our Lens: Social and Emotional Intervention Researc...mentioning
confidence: 99%
“…In addition, failure to examine the relevance of interventions across difference can influence its generalizability (Shogren et al, 2018). Thus, we advocate for better representation among research participants and better reporting of participants by researchers, particularly for racial and ethnic groups (Chow et al, 2022; Steinbrenner et al, 2022). For example, in single case design, reporting more comprehensive information about participants allows for a consistent determination about whom the intervention does and does not work for.…”
Section: Shifting Our Lens: Social and Emotional Intervention Researc...mentioning
confidence: 99%